Relationship between Customer Management Micro, Small and Medium Enterprises (MSMEs) and Marketing Performance in Banten - Suherna Suherna; Titin Nasiatin (Goodwood Publishing, 2023)
Introduction: The current economic crisis in Indonesia, micro, small, and medium-sized enterprises (MSMEs) have proven to be very resilient. When expanding a nation's economy, micro, small, and medium-sized businesses (MSMEs) play a crucial and vital role, so that’s why the researcher want to know about The aim of this research is to see the influence of customer relationship quality on the marketing performance of MSMEs. Materials and Methods: Sampling from food and beverage MSMEs in Banten province. The sample size was 209 respondents. Data collection using a questionnaire with direct interviews with respondents. Secondary data was obtained from BPS Banten Province. analysis technique using the SEM method Results: There is a relationship between Micro, Small and Medium Enterprises (MSME) Customer Management and Marketing Performance with a p value above 0.05.